THE INFLUENCE OF PRODUCT PROMOTION ON THE DECISION TO USE QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) AT STARBUCKS MEDAN CITY - Sarah Elicia Roitona Gultom (The American Journal of Interdisciplinary Innovations and Research, 2024)
This research aims to examine the influence of product promotions on the decision to use QRIS (Quick Response Code Indonesian Standard) at Starbucks in Medan City. The research was conducted at five Starbucks outlets, namely Starbucks Reserve Deli Park, Starbucks Multatuli, Starbucks Iskandar Muda, Starbucks Cambridge City Square, and Starbucks Sun Plaza Medan. A quantitative approach was used with probability sampling techniques to collect data from a minimum of 100 respondents. Indicators used to measure promotions include frequency, quality, quantity, time and suitability of promotions. Meanwhile, usage decisions are measured based on priority of use, ease of access, consideration of benefits, and confidence in using QRIS. The collected data was analyzed using linear regression to determine the relationship between these variables. The research results show that product promotions have a significant influence on the decision to use QRIS at Starbucks. The frequency and quality of promotions are the most dominant factors influencing consumer decisions. These findings suggest that effective and well-targeted promotional strategies can increase QRIS adoption by Starbucks consumers, which in turn can increase transaction efficiency and customer satisfaction.